Produção de pepino japonês ‘Tsuyataro’ enxertado em abóboras ‘Keeper’ e ‘Potent’ - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The cucumber is a native species from India, has an herbaceous and annual habit. The fruit has different sizes, shapes and flavor. It is preferably cultivated in places with temperatures above 20 °C, as it is sensitive to low temperatures and does not tolerate frost. The cultivation of few species and generally of the same family, combined with the continuous use of the soil and inadequate management, causes an incidence of pests and diseases in these cropping systems. Due to these problems, producers have used new production systems, adopting, in some cases, cultural techniques such as grafting on resistant materials as a short-term solution as a control method. The success of the grafting results from the intimate contact between the graft plant, which will develop the aerial part, and the rootstock plant responsible for the root system. The objective of this study was to evaluate the effect of grafting on the growth and development of plants and on resistance to growing conditions. Two hybrids (Keeper and Potent) and a pumpkin cultivar ('Menina Rajada') were used as rootstock for grafting of Tsuyataro hybrid cucumber. The experiment compared the performance of the cucumber hybrid grafted on rootstocks, in addition to cucumber without grafting. The experiment was conducted in randomized blocks with seven blocks per treatment. The evaluations were carried out in the useful area of all plots. In the evaluation done at the transplantation and at 30 days after the transplantation, there were no significant differences for the plant height, except when measured at 45 days after the transplantation, where the rootstock of the hybrid pumpkin 'Keeper' obtained slower development, with 76 cm of height. The variables flowering beginning, fruit length, fruit mean diameter, fruit mean weight, fruit peel color and yield per plant were not significantly different, therefore, the rootstocks used did not differ statistically in relation to those obtained from plants without grafting. It was concluded that the use of grafting in the cucumber crop was not recommended if the soil is free of pathogens that cause disease in the plant's stem and root system.
Keywords: Cucumis sativus L.; Cucurbitaceas; Porta-enxerto; Hortaliças; Rootstock; Vegetables; CNPQ::CIENCIAS AGRARIAS